Linguistic economy and slang as used by Jordanians on Twitter - Abdullah Dawaghreh; Mustafa Suliman (Universitas Syiah Kuala, 2024)
In the context of the rapidly expanding technological landscape, social media platforms have become arenas for innovative communication. This study focuses on the linguistic strategies employed by Jordanian Twitter users within the framework of Computer Mediated Communication (CMC), considering the concept of linguistic economy. The data for this study were derived from 300 tweets, employing digital ethnography for virtual fieldwork. There were a number of 15 users randomly selected for interviews to further understand their language use on Twitter. Employing the descriptive qualitative content analysis, the following linguistic strategies were found in this study, they are Romanized Jordanian Arabic, code-switching, linguistic economy (shortening, contractions, clipping, and acronyms), and slang (repetition, onomatopoeia, cacography, and capitalization). The prevalence of Jordanian Romanized Arabic and strategic code-switching demonstrated users' adaptability in navigating Twitter's language. The study highlighted the dominant role of linguistic economy within the 160-character limit, with users employing strategies such as shortening, contractions, clipping, and acronyms. Expressive techniques like repetition, onomatopoeia, cacography, and capitalization were identified as creative ways to convey emotions and attitudinal meanings. Overall, this research contributes valuable insights into the developing language dynamics on social media, offering insight into the intricate ways users shape communication in the digital age.